Therapeutic Communication Phases and Patient Satisfaction in Meeting Basic Care Needs: A Cross-Sectional Study in Inpatient Care - Rolasnih Lilista Simbolon; Dina Afriani; Petra Diansari Zega; Dewi Sartika Hutabarat; Herna Rinayanti Manurung; Elisabet Manik; Risna Risna (Jurnal Kesehatan dan Kedokteran, 2026)
Therapeutic communication is a core nursing competency that influences patient perceptions of care quality, comfort, safety, and the fulfillment of basic needs during hospitalization. However, evidence remains limited regarding how each phase of therapeutic communication contributes differently to patient satisfaction in inpatient settings. Objective: This study aimed to analyze the relationship between therapeutic communication phases orientation, working, and termination and patient satisfaction in fulfilling basic care needs among inpatients at Mitra Sejati General Hospital, Medan. Methods: A quantitative analytical study with a cross-sectional design was conducted from January to March 2024. The sample consisted of 71 inpatients selected using consecutive sampling. Data were collected through structured questionnaires administered via interviews and analyzed using descriptive statistics and Spearman’s rho correlation test with a significance level of α = 0.05. Findings: Therapeutic communication was generally rated as good across phases, yet patient satisfaction was predominantly neutral (52.1%). Significant positive correlations were found between the orientation phase and patient satisfaction (rₛ = 0.911; p < 0.001) and between the working phase and patient satisfaction (rₛ = 0.787; p = 0.003), while the termination phase showed no significant relationship (rₛ = −0.134; p = 0.265). Implications: The findings highlight the importance of strengthening trust-building communication at the initial and active stages of care. Hospitals should prioritize communication training and clinical protocols that emphasize admission interactions and continuous engagement to improve patient satisfaction and care quality. Originality/Value: This study demonstrates that therapeutic communication phases contribute unequally to patient satisfaction and identifies the orientation phase as the most dominant relational component in the inpatient context, offering new insights for patient-centered nursing practice in Indonesia.